Nursing of integrated Traditional Chinese and western medicine for a patient with gingival carcinoma treated by photodynamic therapy using bronchoscopy (经气管镜光动力治疗牙龈癌1例的中西医结合护理) - WANG Lu (王璐); ZHANG Ruiyun (张瑞芸); WANG Pengfei (王鹏飞); YANG Rong (杨蓉); CHENG Gaiping (成改萍); SUN Na (孙娜) (中西医结合护理)
This paper summarized the clinical data and nursing experience of a patient with gingival carcinoma treated by photodynamic therapy using bronchoscopy. Nursing plan consisted of various interventions such as basic nursing, psychological care, avoiding sunlight, illness observation, pain control, dietary care, Traditional Chinese Medicine nursing technique and health guidance before discharge. On the basis of clinical treatment, individualized nursing of integrated Traditional Chinese and western medicine is effective to improve the therapeutic effect, reduce the risk of post-operative complications and improve the patient satisfaction and post-operative quality of life. (本文回顾了1例经气管镜行光动力治疗牙龈癌患者的临床资料, 总结相关护理措施, 包括基础护理、心理护理、避光教育、病情观察、疼痛护理、饮食护理、中医护理和出院指导。在临床治疗基础上, 通过个体化中西医结合的护理措施干预, 有效提高了治疗效果, 改善患者生活质量, 降低并发症发生风险, 进一步提高临床护理满意度。)